Comparison of three methods for measuring psoriasis severity in clinical studies (Part 1 of 2): change during therapy in Psoriasis Area and Severity Index, Static Physician's Global Assessment and Lattice System Physician's Global Assessment. (27th April 2015) - Chow, C.; Simpson, M.J.; Luger, T.A.; Chubb, H.; Ellis, C.N.
Abstract Background Accurate and reliable assessment of changes in psoriasis severity is critical in clinical trials of therapies. Objective To compare Psoriasis Area and Severity Index (PASI), static Physician's Global Assessment (sPGA), and the Lattice System Physician's Global Assessment (LS‐PGA) in a trial of systemic treatments for plaque psoriasis vulgaris and to assess whether they measure change in psoriasis induced by therapy. Methods Patients were randomized to voclosporin or cyclosporine for 24 weeks (the '24‐week‐treatment' group, n = 366), or placebo for 12 weeks followed by voclosporin for 12 weeks (the 'initial‐placebo' group, n = 89). Results All scoring systems changed in concert and were sensitive enough to detect reductions in severity during placebo therapy as well as with active therapy (P < 0.01 for each measurement). At study onset, there were poorer correlations of sPGA with PASI (r = 0.45) and LS‐PGA (r = 0.39) than between PASI and LS‐PGA (r = 0.68). After therapy, all correlations were stronger, but sPGA continued to be less well correlated (with PASI, r = 0.85; with LS‐PGA, r = 0.79) than LS‐PGA with PASI (r = 0.90). Two‐ or three‐step improvements in LS‐PGA showed very good to excellent accuracy in corresponding to PASI‐50 and PASI‐75, respectively, and were more accurate than comparable changes in sPGA. Conclusion PASI, sPGA and LS‐PGA are responsive to the varying degrees of improvement in psoriasis induced by either placebo or active therapy. While the three systems capture similar information, each has different reasons for use in a clinical trial.